Evaluation of Aquarium Antibiotic Formulations - Trust, T. J. (1974)
The antibacterial activity of eight products marketed for the therapy and prophylaxis of diseases of ornamental fishes was tested. The products contained erythromycin, neomycin, a nitrofuran, penicillin, sulfa compounds, streptomycin, or tetracycline. When used at the concentration recommended by the manufacturer, the products failed to inhibit the growth of bacterial species known to be potential pathogens of ornamental fishes and failed to reduce significantly the bacterial numbers in water containing fish. Concentrations of the products that were bacteriostatic were markedly higher than the in-use concentration recommended by the manufacturer. The danger presented by the unrestricted availability of antibiotic compounds frequently used in the treatment of human and animal disease is discussed.